2009
DOI: 10.1192/pb.bp.107.018861
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of parental mental illness in Australian families

Abstract: Aims and MethodTo provide multiple estimates of the numbers of Australian and Victorian families and children living in families where a parent has had a mental illness. We used the Australian Bureau of Statistics Victorian Mental Health Branch service usage and data collected from 701 community participants to triangulate prevalence information.ResultsAccording to population estimates, 23.3% of all children in Australia have a parent with a non-substance mental illness, 20.4% of mental health service users ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
136
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(150 citation statements)
references
References 13 publications
6
136
1
2
Order By: Relevance
“…National survey studies have reported that between 12.1 and 38.5 % of the total child population has a parent with a mental illness (Bassani et al 2008;Bool et al 2007;Maybery et al 2009). About one-third of these children experience transient mental problems and another third experience more serious and long-term adjustment issues (Mowbray et al 2004;Ostman and Hansson 2002;Rutter and Quinton 1984).…”
Section: Introductionmentioning
confidence: 96%
“…National survey studies have reported that between 12.1 and 38.5 % of the total child population has a parent with a mental illness (Bassani et al 2008;Bool et al 2007;Maybery et al 2009). About one-third of these children experience transient mental problems and another third experience more serious and long-term adjustment issues (Mowbray et al 2004;Ostman and Hansson 2002;Rutter and Quinton 1984).…”
Section: Introductionmentioning
confidence: 96%
“…This suggests that up to one in five young people live in families in which a parent has a mental illness. 4 …”
Section: Prevalence: Families and Childrenmentioning
confidence: 99%
“…3 Another study specifically examined child, as opposed to parent, prevalence in three ways. 4 First, Australian Bureau of Statistics data showed that 23.3% of all Australian children lived in a family with a parental mental illness. Second, Mental Health Branch service-use data for the 2003-04 financial year indicated that across Victoria, 20.4% of patients had an estimated 14 403 children.…”
Section: Prevalence: Families and Childrenmentioning
confidence: 99%
“…Twenty-one to 23% of young people in Australia are estimated to have at least one parent with a mental illness [5]. Hence, these young people are a highly prevalent, high-risk group that warrant effective intervention to prevent or reduce the increased risks of adverse outcomes associated with parental mental illness.…”
Section: Introductionmentioning
confidence: 99%